cGAS/STING in skin melanoma: from molecular mechanisms to therapeutics - Jafaridarabjerdi Mahin; Xuezhu Xu; Ling Li; Cong Zhang (Cell Communication and Signaling)
Abstract Melanoma, recognized as the most aggressive type of skin cancer, has experienced a notable increase in cases, especially within populations with fair skin. This highly aggressive cancer is largely driven by UV radiation exposure, resulting in the uncontrolled growth and malignant transformation of melanocytes. The cGAS-STING pathway, an immune signaling mechanism responsible for detecting double-stranded DNA in the cytoplasm, is essential for mediating the immune response against melanoma. This pathway serves a dual purpose: it enhances antitumor immunity by activating immune cells, but it can also promote tumor growth when chronically activated by creating an immunosuppressive environment. This review comprehensively examines the multifaceted implication of the cGAS-STING pathway in melanoma pathogenesis and treatment. We explore its molecular mechanisms, including epigenetic regulation, interaction with signaling pathways such as AR signaling, and modulation by various cellular effectors like TG2 and activin-A. The therapeutic potential of modulating the cGAS-STING pathway is highlighted, with promising results from STING agonists, combination therapies with immune checkpoint inhibitors, and novel drug delivery systems, including nanoparticles and synthetic drugs. Our findings underscore the importance of the cGAS-STING pathway in melanoma, presenting it as a critical target for enhancing anti-tumor immunity. By leveraging this pathway, future therapeutic strategies can potentially convert ‘cold’ tumors into ‘hot’ tumors, making them more susceptible to immune responses.